2020
DOI: 10.1186/s40001-020-00450-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of a quantitative segmentation model to assess the effect of comorbidity on patients with COVID-19

Abstract: Background The coronavirus disease 2019 (COVID-19) has brought a global disaster. Quantitative lesions may provide the radiological evidence of the severity of pneumonia and further to assess the effect of comorbidity on patients with COVID-19. Methods 294 patients with COVID-19 were enrolled from February, 24, 2020 to June, 1, 2020 from six centers. Multi-task Unet network was used to segment the whole lung and lesions from chest CT images. This deep learning method was pre-trained in 650 CT images (550 in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…An initial prospective made by Huang et al [12] on chest CT scans of patients affected by COVID-19 has shown that the examined subjects have a bilateral GGO and CS. The same medical results were also confirmed by other authors [13,14], who posed the basis for the next quantification studies allowing a better characterization of the COVID-19 features. The classification between early-stage patients and progressive phases has been thoroughly investigated [15][16][17][18], and all of them lead to the same conclusion: the main COVID-19 features can be difficult to detect in early stages of the disease, and their correct identification is strongly dependent on the radiologist's expertise.…”
Section: Introductionsupporting
confidence: 79%
“…An initial prospective made by Huang et al [12] on chest CT scans of patients affected by COVID-19 has shown that the examined subjects have a bilateral GGO and CS. The same medical results were also confirmed by other authors [13,14], who posed the basis for the next quantification studies allowing a better characterization of the COVID-19 features. The classification between early-stage patients and progressive phases has been thoroughly investigated [15][16][17][18], and all of them lead to the same conclusion: the main COVID-19 features can be difficult to detect in early stages of the disease, and their correct identification is strongly dependent on the radiologist's expertise.…”
Section: Introductionsupporting
confidence: 79%
“…Differently from the previous study, Zhang et al included hypertension-the most common, COPD and cerebrovascular diseases in addition to DM, already described as major risk factors [126]: authors found a significant correlation with age, length of incubation period, abnormal laboratory findings and severity status. Moreover, a higher number of comorbidities resulted in a higher number of CT lesions, especially in presence of DM as main risk factors for lung volume involvement [127].…”
Section: Ai In the Stratification And Definition Of Severity And Complications Of Covid-19 Pneumonia At Chest Ctmentioning
confidence: 99%
“…AI has demonstrated its potential in assisting the diagnosis of COVID-19, and its corresponding application in computer-aided diagnosis has successfully improved diagnostic efficiency in many applications. The current literature mainly focuses on revealing AI’s potentiality in assisted diagnosis [ 44 48 ], and some in segmentation [ 49 , 50 ]. More specifically, to address the difficulty of emerging false positives in CT findings, Lin et al trained a 2D convolutional neural networking (CNN) method to differentiate COVID-19 from community-acquired pneumonia and non-pneumonia [ 51 ].…”
Section: Ai In Covid-19mentioning
confidence: 99%